Adaptation Mechanisms and Resilience of Small-Scale Fishermen’s Livelihoods to the Impacts of Climate Variability in Central Tapanuli Regency, North Sumatra - anugerah, Tirta; Simanjuntak, Asnika; Sarifuddin, Andri; Mahaji, Toga; Rangganis, Syafira Aulia; Fitri, Mutiara; Siburian, Juliana Pebrina; Khobir, Muhammad Latiful; Susanti, Nelvia Mai (International Journal of Marine Engineering Innovation and Research, 2026)
Climate variability is increasing the vulnerability of small-scale fishing communities, especially in coastal areas that are highly dependent on fishery resources as their main source of livelihood. This study aims to identify fishermen's adaptation mechanisms, analyze their level of resilience, and determine the factors that influence the resilience of small-scale fishermen in two coastal villages in Central Tapanuli Regency, namely Teluk Roban Village and Pasar Sorkam Village. This study uses a quantitative survey approach with purposive sampling techniques on 70 fishing households consisting of 35 fishermen in Teluk Roban Village and 35 fishermen in Pasar Sorkam Village. The data were analyzed using statistical analysis to identify factors that influence the resilience of fishing households. The results of the study show that the resilience of fishing households in Teluk Roban Village is significantly influenced by education levels, access to financial institutions, livestock ownership, and the size of the fishing fleet. Meanwhile, the resilience of fishing households in Pasar Sorkam Village is more influenced by the age of the head of the family, non-fishing income and access to natural capital such as mangrove forests, rice fields, and mango and coconut trees. Despite differences in livelihoods, the level of resilience of fishing households in both villages does not show significant differences and is generally in the moderate category. These findings indicate that diversification of livelihoods, access to financial resources, and utilization of natural capital are important factors in strengthening the adaptive capacity of fishing households to climate variability.